2014
DOI: 10.1093/schbul/sbu040
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Bad Things Happen to Me? Attributional Style, Depressed Mood, and Persecutory Delusions in Patients With Schizophrenia

Abstract: Theoretical models postulate an important role of attributional style (AS) in the formation and maintenance of persecutory delusions and other positive symptoms of schizophrenia. However, current research has gathered conflicting findings. In a cross-sectional design, patients with persistent positive symptoms of schizophrenia (n = 258) and healthy controls (n = 51) completed a revised version of the Internal, Personal and Situational Attributions Questionnaire (IPSAQ-R) and assessments of psychopathology. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 40 publications
(57 reference statements)
0
28
0
2
Order By: Relevance
“…Unpublished data from 6 studies were obtained. (41)(42)(43)(44)(45)(46) Studies were published between 1991 and 2016; half (k = 32) were conducted in the United Kingdom, with the remainder occurring in Europe (k = 17), United States and Canada (k = 10) and Australia (k = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Unpublished data from 6 studies were obtained. (41)(42)(43)(44)(45)(46) Studies were published between 1991 and 2016; half (k = 32) were conducted in the United Kingdom, with the remainder occurring in Europe (k = 17), United States and Canada (k = 10) and Australia (k = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, social cognitive impairments found are not only in schizophrenia but already during prodromal stages of the illness during which, in particular, alterations of attributional biases can already be detected [92]. Differences in attributional style have been thought to play an important role in the formation and maintenance of persecutory ideations and other positive symptoms [93].…”
Section: (D) the Case Of Schizophreniamentioning
confidence: 99%
“…Similarly, several longitudinal studies have confirmed that depressive symptomatology may appear parallel to improvement in insight during the natural course of psychotic exacerbation (Wiffen et al, 2010;Parellada et al, 2011, Johnson et al, 2012Schennach et al, 2012). To date, various theoretical frameworks and psychological mechanisms have been proposed as mediators between better insight and depressive symptomatology including self-stigmatization (Lysaker et al, 2007;Cavelti et al, 2012), hopelessness and reduced self-esteem (Drake et al, 2004;Schrank et al, 2014), feelings of a lack of control over the illness (Birchwood et al, 1993), metacognitive abilities (Lysaker et al, 2013) as well as attribution and attachment styles (Mehl et al, 2014).…”
Section: Discussionmentioning
confidence: 96%